Analisis Kerja Keras dalam Mata Pelajaran Fisika di SMAN 1 Kota Jambi - Endah Febri Setiya Rini; Riska Fitriani; Wita Ardina Putri; Agnes Aktapianti Br. Ginting; Maria Marisa Matondang (SAP (Susunan Artikel Pendidikan), 2021)
The character of hard work is a character that must not be vanished, especially for students at the end of class XII Senior High School. This study aimed to determine the results of the character of hard work description in physics subjects in class XII MIPA at SMAN 1 Jambi City. This study used a quantitative approach. This type of research was a survey with a research instrument in the form of a questionnaire. The sampling technique used in this study was simple random sampling. The subjects of this study were students of class XII MIPA 1, 2, and 3 in the 2020/2021 school year, with a total of 60 respondents. The data analysis technique in this study used the SPSS program. The results showed that the hard work questionnaire in physics was classified as "good". The number of students who had a hard work character which was categorized as very good resulted in a percentage of 8.3%. Meanwhile, the number of students who got the good category resulted in a percentage of 91.7%. With this research, hopefully, it can contribute as knowledge for the writer and teacher concerned to improve the character of hard work in physics subjects at SMAN 1 Jambi City.